DYSTOCIA DUE TO LATERAL DEVIATION OF HEAD IN MARE – A CASE REPORT - SINGH, GYAN; CHAUDHARY, R N; YADAV, RISHIPAL; YADAV, POOJA; NIWAS, RAM; DHAMIWAL, DINESH; PANIHAR, SANDEEP; DANGI, PARDEEP; SAINI, GITESH; SINGH, HARENDER (The Indian Journal of Animal Reproduction, 2020)
A case of dystocia in a mare with longitudinal presentation, dorso-sacral position with lateral deviation of headand bilateral knee flexion was presented in Veterinary Clinical Complex of the university and was resolved by caesareansection under gaseous anaesthesia.
Keywords: Caesarean section; Dystocia; flexion of knee joint; lateral deviation of head